Survei Kondisi Sosial Masyarakat Dalam Memenuhi Kebutuhan Air harian di Kecamatan Minas, Kabupaten Siak - Maulana Hardi; Yusni Ikhwan Siregar; Mirna Ilza; Sofia Anita (Dinamika Lingkungan Indonesia, 2019)
Water is the most abundant chemical compound in nature, but in line with the increasing standard of living, the need for water also increases so that water becomes an expensive item. In some areas, it is not easy to get clean water sources that are free from pollution because high of domestic activities and water also sucked up a lot by industrial activities which require a lot of water for their production. On the other hand, land which is a water bank has been covered a lot by housing, industry, regardless of the function of the land as a vehicle for water storage. Increasing industrial and community activities can also increase the risk of pollution which can reduce the quality of existing water sources and cause difficulties for the community to meet their daily water needs. In this study, field surveys and questionnaires were conducted to obtain information about the social conditions of the community in meeting their daily water needs for drinking water and clean water. Laboratory test also conducted to evaluate the quality of water source based on regulation Peraturan Pemerintah No 82 tahun 2001. The results of the study showed that the community in Minas area still could not meet the daily water needs properly in terms of quality and quantity.